The theme Generalization of the theoretical aspects of interpretation - Alieva Dilafruz Mukhtarovna (Genius Journals, 2025)
The article analyzes modern scientific ideas about interpretation, in particular about the interpretation of a text message; different approaches to the interpretation and content of this concept are compared, a conclusion is made about the significance of interpretation for the process of teaching reading. Text, interpretation, perception, interpretation, interpretation, hermeneutics, psycholinguistics, significat, speechthinking activity
Keywords: interpretation; perception; psycholinguistics